Australian Patriography: How Sons Write Fathers in Contemporary Life Writing, Stephen Mansfield (Journal of the Association for the Study of Australian Literature, 2014)
Australian Patriography: How Sons Write Fathers in Contemporary Life Writing, Stephen Mansfield